2001
DOI: 10.1007/s004670100585
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis access induced limb ischemia corrected using quantitative duplex ultrasound

Abstract: Dialysis access induced limb ischemia (DAILI) is a rare complication after the creation of an arteriovenous fistula in infancy but can cause irreversible ischemic limb damage in severe cases. The incidence of DAILI is higher in bridge graft fistulas than in native fistulas. DAILI patients may be managed by surgically reducing the volume flow in the fistula. However, in the pediatric age group, such a reduction of volume flow may result in thrombosis or an inadequate flow for effective dialysis. Several methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…3,7 Blood flow in an autogenous access should be Ͼ600 mL/min for efficient hemodialysis but can decrease to 300 to 500 mL/min while still maintaining access patency. 14 The blood flow in most patients exceeds this value and simple banding guided by quantitative Doppler ultrasound imaging may improve hand perfusion while reducing blood flow in the access to the minimum flow needed to maintain patency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7 Blood flow in an autogenous access should be Ͼ600 mL/min for efficient hemodialysis but can decrease to 300 to 500 mL/min while still maintaining access patency. 14 The blood flow in most patients exceeds this value and simple banding guided by quantitative Doppler ultrasound imaging may improve hand perfusion while reducing blood flow in the access to the minimum flow needed to maintain patency.…”
Section: Discussionmentioning
confidence: 99%
“…The blood flow in the fistula was gradually reduced by manual compression until a digital pressure of at least 60 mm Hg and/or a digital/brachial pressure index of Ն0.5 was attained, to a minimum flow of 350 mL/min. 7 Digital pressure was measured with a digital blood pressure cuff and a Doppler probe. If these results could not be achieved with a minimum flow of 350 mL/min, then more complex surgical interventions or access closure had to be considered.…”
Section: Details Of the Proceduresmentioning
confidence: 99%
“…Ischemic steal syndrome causing symptoms after fistula creation is rare, but challenging to manage (12). The options for treating vascular access induced distal limb ischemia include elimination of the fistula, reducing the flow in the fistula with maintained patency, and ligation of the source of steal with distal revascularization (14). Should one believe that early intervention and correction of vascular access induced ischemia improves longevity of the fistula and patient outcome, thermography might be used for the timely detection of patients (children) at risk for developing symptoms of hand ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Small children may present with nonspecific symptoms, such as restlessness, a painful appearance, or a motionless hand. Imaging with Doppler ultrasound or arteriography can provide data on proximal inflow and outflow disease, as well as fistula flow rates (13,14). Several noninvasive physiological techniques are used to define pressure and flow distal to the fistula to quantify the extent of steal, namely, digital plethysmography, pulse volume recordings, digital pressure index, and systolic pressure index (12).…”
mentioning
confidence: 99%
“…Steal syndrome is a well-Czupryniak/Kałuż yń ska/Nowicki/Więcek/ Bald/Owczarek known complication of AV access. Morsy et al [1] and Hirschl et al [5] observed ischemic changes in the fingers of a shunt limb, and in 2001, Shemesh et al [6] coined the term 'dialysis access induced limb ischemia (DAILI) syndrome'. However, HD patients often complain about feeling of cold and numbness not only in the AV shunt limb but in both hands [7].…”
mentioning
confidence: 99%